2008
DOI: 10.1002/pssc.200778641
|View full text |Cite
|
Sign up to set email alerts
|

Realization of AlGaN/GaN HEMTs on 3C‐SiC/Si(111) substrates

Abstract: Cubic SiC/Si (111) template is an interesting alternative for growing GaN on silicon. As compared with silicon, this substrate allows reducing the stress in GaN films due to both lower lattice and thermal expansion coefficient mismatch, and can provide better heat dissipation. In this work, we first developed the epitaxial growth of 3C‐SiC films on 50 mm Si(111) substrates using chemical vapor deposition. AlGaN/GaN high electron mobility transistors were grown by molecular beam epitaxy on these films. Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…So far, it has been reported that a stable 3C-SiC intermediate layer can be introduced in between GaN and Si to suppress the crack generation and enhance the crystal quality of the GaN film on Si substrate [14], [17]- [20]. Owing to the above fact, a thick nitride layer can be grown on Si by introducing a 3C-SiC intermediate layer [14], [20].…”
Section: Introductionmentioning
confidence: 99%
“…So far, it has been reported that a stable 3C-SiC intermediate layer can be introduced in between GaN and Si to suppress the crack generation and enhance the crystal quality of the GaN film on Si substrate [14], [17]- [20]. Owing to the above fact, a thick nitride layer can be grown on Si by introducing a 3C-SiC intermediate layer [14], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Such a material is SiC, firstly employed by Takeuchi and Davis . Later, micrometer thick 3C‐SiC(111) layers were used for the same purpose . Albeit, it was shown that for reliable heteroepitaxial growth and device fabrication thick silicon carbide layers are not necessary .…”
Section: Introductionmentioning
confidence: 99%